PERTUMBUHAN TANAMAN SENGON (PARASERIANTHES FALCATARIA L.) TERINFEKSI MIKORIZA PADA LAHAN TERCEMAR Pb. - Triono Bagus Saputro; Nurul Alfiyah; Dian Fitriani (JURNAL SOSIAL HUMANIORA (JSH), 2016)
Paraserianthes falcataria plant is well known to be capable to make an excellent association and symbiosis with mycorrhizae. Mycorrhizae can improve the plant's ability to survive in heavy metal contaminated land, one of which is Pb (lead). Pb is the main heavy metal pollutants in all environments. This aims of this research were to determine the accumulation of Pb on sengon plant roots and its   growth in Pb contaminated media. This research uses a completely randomized design. Pb(NO3)2 were given at a dose of 833 mg/kg and the concentration of mycorrhizal inoculation of Glomus sp. used were 25, 50 and 75 grams of mycorrhizae. The measured parameters were plant height, root length, plant dry weight, accumulation of Pb in roots, chlorophyll and protein profile test. The results showed that 75 grams of mycorrhizal Glomus sp. were the highest on several parameters including plant height, dry weight, root length. The chlorophyll content were grown on media containing Pb with each value of 77.5 cm; 17.86 grams; 31.5 cm; 8.99 g/ml. A dose of 75 grams of Glomus sp. also increased the absorption and accumulation of Pb in the roots with 3.60 ppm. while the protein electrophoresis show the specific band in P. falcataria  that exposed to Pb with molecular weight 53.67 kDa.